The Educational Institution Policies as Forms of Social Conflict: A Phenomenological Study - Sa'adah, Khoridatus (Universitas Nahdatul Ulama Surabaya, 2024)
Differences in the implementation of education policies certainly have an impact on different results. Such is the case with the portrait of education in Payaman village. The implementation of education policy, which should have a good impact, actually causes conflict. Conflicts arise between educators and policy makers, in this case the foundation board. The purpose of this study is to determine the process and form of conflict that occurs between educators and policy makers. The type of research used is qualitative. Data collection was done by interview method and literature study. The theory used is conflict from Ralf Dahrendorf with the rationalization that authority and position form a society that is forcibly coordinated so that it has an impact on the conflict formed. The results showed that the implementation of education policy in the form of regulations on the obligation of educators' children to attend educational institutions where parents as educators teach. Education policy only binds educators from ordinary groups. Policy makers are not bound by the policy, causing social jealousy. The result is conflict between educators and policy makers. The conflict takes the form of a closed dispute due to the difference in social status between the two.